Cyclic fatigue resistance of M-Pro and RaCe Ni-Ti rotary endodontic systems in curved canals : A comparative in vitro study - Hadeer Mostafa Elmohamady Elfeky; Khaled Mohamed Ezzat Mohamed; Marwa Mahmoud Ali Bedier (Cairo : Hadeer Mostafa Elmohamady Elfeky, 2019)
Objectives: To compare the flexural cyclic fatigue resistance and the length of the fractured segments (FLs) of recently introduced M-Pro rotary files with that of RaCe rotary files in curved canals and to evaluate the fracture surface by scanning electron microscopy (SEM). Materials and Methods: Thirty-six endodontic files with the same tip size and taper (size 25, 0.06 taper) were used. The samples were classified into 2 groups (n = 18): the M-Pro group (M-Pro IMD) and the RaCe group (FKG). A custom-made simulated canal model was fabricated to evaluate the total number of cycles to failure and the FL. SEM was used to examine the fracture surfaces of the fragmented segments.The data were statistically analyzed and comparisons between the 2 groups for normally distributed numerical variables were carried out using the independent Student's t -test. A p value less than 0.05 was considered to indicate statistical significance. Results: The M-Pro group showed significantly higher resistance to flexural cyclic fatigue than the RaCe group ( p< 0.05), but there was no significant difference in the FLs between the 2 groups ( p {u2265} 0.05). Conclusions: Thermal treatment of nickel-titanium instruments can improve the flexural cyclic fatigue resistance of rotary endodontic files, and the M-Pro rotary system seems to be a promising rotary endodontic file
Thesis (M.Sc.) - Cairo University - Faculty of Oral and Dental Medicine - Department of Endodontics
Issued also as CD
Keywords: Canals; Flexural resistance; Fracture